2021
DOI: 10.3389/fevo.2021.646702
|View full text |Cite
|
Sign up to set email alerts
|

The Silent Threat of Non-native Fish in the Amazon: ANNF Database and Review

Abstract: Non-native fish (NNF) can threaten megadiverse aquatic ecosystems throughout the planet, but limited information is available for the Amazon Region. In this study we review NNF data in the Amazonian macroregion using spatiotemporal records on the occurrence and the richness of NNF from a collaborative network of 35 regional experts, establishing the Amazon NNF database (ANNF). The NNF species richness was analyzed by river basin and by country, as well as the policies for each geopolitical division for the Ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 64 publications
0
26
0
2
Order By: Relevance
“…regions where species richness is higher (in particular Africa, Indomalayan and South America) were underrepresented. These regions with high biodiversity are increasingly threatened by different anthropogenic pressures including biological invasions (Doria et al 2021). We believe that the development of studies with adequate control (including space‐for‐time and time sequence approach together), along with more studies in the tropics, is necessary to fill these gaps and improve our comprehension of the effects of non‐native species on different aspects of native diversity, including community's homogenization.…”
Section: Discussionmentioning
confidence: 99%
“…regions where species richness is higher (in particular Africa, Indomalayan and South America) were underrepresented. These regions with high biodiversity are increasingly threatened by different anthropogenic pressures including biological invasions (Doria et al 2021). We believe that the development of studies with adequate control (including space‐for‐time and time sequence approach together), along with more studies in the tropics, is necessary to fill these gaps and improve our comprehension of the effects of non‐native species on different aspects of native diversity, including community's homogenization.…”
Section: Discussionmentioning
confidence: 99%
“…(Miranda-Chumacero et al 2012). A recent review revealed 1,314 records of non-native fish species (in 9 orders and 17 families), in the Amazon Basin since the first record in 1939, with a sharp increase in the last 20 years (75% of occurrences) (Doria et al 2021). Non-native species were mainly introduced by the ornamental trade, or for aquaculture and sport-fishing.…”
Section: Invasive Speciesmentioning
confidence: 99%
“…Uma revisão da literatura identificou a ocorrência de 192 espécies não nativas em ecossistemas aquáticos continentais neotropicais; entre estas espécies, 12% eram pertencentes à família Cichlidae (Gubiani et al, 2018). Em outra revisão mais atual compreendendo seis países da América do Sul, que cobrem mais de 80% da região Amazônica, foi determinado um aumento temporal na ocorrência de espécies de peixes não nativos, com 41 espécies de peixes registradas, incluindo Cichla monoculus e Cichla piquiti (Doria et al, 2021).…”
Section: Introductionunclassified
“…O interesse econômico pelo aspecto ornamental, a criação de reservatórios, e o fomento da pesca esportiva e da aquicultura extensiva e semiextensiva culminaram na ampla introdução de espécies de tucunarés, a partir da década de 1960, em diversas regiões do Brasil (Gubiani et al, 2018;Doria et al, 2021) e do mundo (Sastraprawira et al, 2020). No entanto, a introdução de espécies não nativas pode resultar em consequências ecológicas severas, evaluating the structure of tucunaré populations themselves.…”
Section: Introductionunclassified